2023
DOI: 10.1002/jmv.28857
|View full text |Cite
|
Sign up to set email alerts
|

Diverse intratumoral heterogeneity and immune microenvironment of two HPV‐related cervical cancer types revealed by single‐cell RNA sequencing

Abstract: Cervical squamous cell carcinoma (SCC) and adenocarcinoma (AD) are the main histological types of human papillomavirus-related cervical cancer. However, there are few reports on cell type-specific molecular differences between SCC and AD.Here, we used unbiased droplet-based single-cell RNA sequencing to elucidate the cellular differences between SCC and AD in tumor heterogeneity, and tumor microenvironment (TME). A total of 61 723 cells from three SCC and three AD patients, were collected and divided into nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Additionally, they present a diminished expression profile in cervical adenocarcinoma compared to squamous cervical carcinoma both in TCGA dataset ( Figures 1M–O ) and the GSE192897 dataset ( Figures 1P–R ). Previous studies demonstrated that cervical adenocarcinoma possessed a heightened malignant propensity, and a greater inclination toward metastatic behavior ( 45 ), characterized by the TME with a more robust immune infiltration cells profile ( 46 ). These findings underscore the pivotal role of the STING pathway in shaping the prognosis of cervical cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they present a diminished expression profile in cervical adenocarcinoma compared to squamous cervical carcinoma both in TCGA dataset ( Figures 1M–O ) and the GSE192897 dataset ( Figures 1P–R ). Previous studies demonstrated that cervical adenocarcinoma possessed a heightened malignant propensity, and a greater inclination toward metastatic behavior ( 45 ), characterized by the TME with a more robust immune infiltration cells profile ( 46 ). These findings underscore the pivotal role of the STING pathway in shaping the prognosis of cervical cancer.…”
Section: Resultsmentioning
confidence: 99%
“…3e (full names of the cancers are detailed in Supplementary Table 15 ), where it can be seen that the marker candidates identified using this strategy are consistent with available knowledge. For instance, EPCAM, KRT8, KRT18 are widely employed markers for malignant cell or cancer stem cell across various malignancies such as cervical cancer 37 , breast cancer 38 and head & neck cancer 39 , and SOX2 was considered as a cancer markers in glioblastomas 40 and esophageal squamous cell carcinoma 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the advancements and application of single-cell sequencing and deep learning networks have provided additional potential biomarkers for the diagnosis and prognosis of HPV-related tumors. 17 Traditional treatment modalities for CC include surgery, chemotherapy, radiotherapy, and targeted immunotherapy. In recent years, new therapies such as immune checkpoint inhibitors (ICIs), antiangiogenic agents, and therapeutic vaccines have emerged, resulting in a significant improvement in survival rates and prognosis for CC patients.…”
Section: The Mechanisms Of Hpv Action and The Related Factors In Clin...mentioning
confidence: 99%